2019
DOI: 10.1111/1365-2745.13250
|View full text |Cite
|
Sign up to set email alerts
|

Grassland restoration characteristics influence phylogenetic and taxonomic structure of plant communities and suggest assembly mechanisms

Abstract: Phylogenetic and species‐based taxonomic descriptions of community structure may provide complementary information about the mechanisms driving community assembly across different environments. Environmental filtering may have similar effects on taxonomic and phylogenetic diversity under the assumption of niche conservatism, whereas competitive exclusion could produce contrasting patterns in these diversity metrics. In grassland restorations, these diversity patterns might then reveal potential assembly mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 95 publications
4
35
0
Order By: Relevance
“…Khalil et al () was the only other study here suggesting that FD expressed through intraspecific trait variation can be a driver of community assembly, especially if dominant species impact FD of subordinate species. In contrast, Barber et al () found no impact of environmental gradients such as restoration age, time since fire, seed mix richness and precipitation in first year of planting on PD, suggesting PD is not a driver or passenger of community assembly.…”
Section: Diversity Can Be Both a Passenger And A Driver Of Community mentioning
confidence: 93%
See 3 more Smart Citations
“…Khalil et al () was the only other study here suggesting that FD expressed through intraspecific trait variation can be a driver of community assembly, especially if dominant species impact FD of subordinate species. In contrast, Barber et al () found no impact of environmental gradients such as restoration age, time since fire, seed mix richness and precipitation in first year of planting on PD, suggesting PD is not a driver or passenger of community assembly.…”
Section: Diversity Can Be Both a Passenger And A Driver Of Community mentioning
confidence: 93%
“…Griffin‐Nolan et al () showed a similar pattern, where changes in FD and PD did not consistently match; as functional traits changed from drought‐tolerance to drought‐avoidance, PD did not differ accordingly. Barber et al () showed that while PD did not change with environmental context, SD did respond to all the environmental gradients they analysed. Lastly, in their systematic review, Cadotte et al () found that while FD and PD are often positively correlated, functional and phylogenetic dispersion sometimes show opposite patterns.…”
Section: Diversity Measures Give Different Complementary Informationmentioning
confidence: 98%
See 2 more Smart Citations
“…As a measure of biodiversity, phylogenetic diversity differs from taxonomic diversity as it takes into account the phylogenetic and evolutionary relationships among taxa based upon distance matrices of pairwise dissimilarities derived from molecular data [15]. Taxonomic and phylogenetic diversity patterns may differ over the course of a restoration reflecting key and heretofore unknown aspects of community assembly [13,16,17].…”
Section: Introductionmentioning
confidence: 99%